2019
DOI: 10.1302/2046-3758.81.bjr-2018-0164.r1
|View full text |Cite
|
Sign up to set email alerts
|

Platelet lysates from aged donors promote human tenocyte proliferation and migration in a concentration-dependent manner

Abstract: ObjectivesPlatelet-rich plasma (PRP) is being used increasingly often in the clinical setting to treat tendon-related pathologies. Yet the optimal PRP preparations to promote tendon healing in different patient populations are poorly defined. Here, we sought to determine whether increasing the concentration of platelet-derived proteins within a derivative of PRP, platelet lysate (PL), enhances tenocyte proliferation and migration in vitro, and whether the mitogenic properties of PL change with donor age.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…Similar results found by Rughetti et al (2008). Anitua et al (2009) and Berger et al (2019), on the other hand, used a PRP volume of 20% and found maximum proliferation rate at 0.767 ± .95 and 0.875 (young group) x 10 6 plt/µL, respectively-about half of Haynesworth et al (2002) and Wang et al (2019). Graziani et al (2006) used the highest PRP/media ratio (33%/67%) and observed maximum proliferation of approx.…”
Section: Giusti Et Al (2014)mentioning
confidence: 93%
See 4 more Smart Citations
“…Similar results found by Rughetti et al (2008). Anitua et al (2009) and Berger et al (2019), on the other hand, used a PRP volume of 20% and found maximum proliferation rate at 0.767 ± .95 and 0.875 (young group) x 10 6 plt/µL, respectively-about half of Haynesworth et al (2002) and Wang et al (2019). Graziani et al (2006) used the highest PRP/media ratio (33%/67%) and observed maximum proliferation of approx.…”
Section: Giusti Et Al (2014)mentioning
confidence: 93%
“…. '' Low ACD CaCl 2 10% of 2.94+/-1.9 × 10 6 2.94+/-1.9 × 10 6 0.875 × 10 6 Berger et al (2019) Leukocyte level: mean 0.1 × 10 3 /µ L (SD 0.1) (Supplementary material) Low CPD Freeze-and-thaw 20% of 0.875 × 10 6 (Young group) 20% of 3.5 × 10 6 (Old group) 3.5 × 10 6 Wang et al (2012) Leukocyte level: 0.37 ± 0.14 ×10 9 /L Leukocyte concentration in PRP significantly lower than that in whole blood (P < 0.001). ( See article Mean optimal PRP concentration 2.7 × 10 6 optimal concentration, respectively.…”
Section: Amable Et Al (2014)mentioning
confidence: 98%
See 3 more Smart Citations